Statins and perihemorrhagic edema in patients with spontaneous intracerebral hemorrhage. (30th April 2019) - Witsch, Jens; Al-Mufti, Fawaz; Connolly, E. Sander; Agarwal, Sachin; Melmed, Kara; Roh, David J.; Claassen, Jan; Park, Soojin
Abstract : Objective: To test the hypothesis that in patients with spontaneous intracerebral hemorrhage (ICH), perihemorrhagic edema to hematoma ratio (rPHE) on admission CT scan (aCT) is unaffected by home statin use when time from symptom onset to aCT is controlled for. Methods: In a single-center prospective cohort of 176 consecutive ICH patients, 2 investigators independently determined hematoma and perihemorrhagic edema (PHE) volumes by using semiautomated validated software. rPHE were dichotomized at the median ratio (>0.75 vs ⩽0.75). We used binary logistic regression to test for associations with rPHE. Results: In patients using statins as home medication before hospital admission (n = 38) compared to patients without prior statin use (n = 138), median PHE volumes were 15.8 mL (interquartile range [IQR] 6.5–39.4) vs 10.8 mL (IQR 5.1–26.8), p = 0.2. rPHE was 0.71 (IQR 0.56–1.0) vs 0.74 (IQR 0.52–1.0), p = 0.79. In a binary logistic regression model, time of aCT relative to symptom onset (odds ratio [OR] 1.02, confidence interval [CI] 1.01–1.12, p = 0.016) and presence of intraventricular hemorrhage on aCT (OR 0.40, CI 0.20–0.78, p = 0.007) were but prior statin use was not (OR 1.17, CI 0.55–2.52, p = 0.68) associated with rPHE. Conclusion: Use of statins before hospital admission for ICH is not associated with reduced rPHE on admission CT. In future studies, imaging timing relative to ICH onset needs to be controlled for in order to avoid confounding.